Strengthening Institutional Social-Economic Institutions Through Bumdes in Pagerharjo Village, Samigaluh District, Kulonprogo Regency - Niken Widyastuti; Diana Anggraini Kusumawati (International Journal of Applied Business and International Management, 2024)
Potential in the area, including institutions, people, and natural resources, should be handled, one of which is BUMDES. BUMDES is an organization that was entrenched based on the needs and possibilities of the village and is run by the community and village government to boost the rural economy. The performance of BUMDES must considerably enhance the welfare of the populace. Under BUMDES's work system, all commercial and community economic activities are facilitated in a professionally managed institution or corporate organization. As a consequence, community companies are successful and fruitful, enabling the best possible management of all village economic endeavors. The purpose of this study is to ascertain the methods used by the Pagerharjo Village, Samigaluh Regency, and the Government to fortify village institutions (BUMDES). The research employs a qualitative descriptive methodology, with findings that highlight the significance of generalization. In an attempt to fully realize the village's potential, BUMDES Binangun Pagerharjo Village has developed into an organization that is capable of boosting the local economy through the establishment of social services, economic business development, and BUMDES institutional strengthening initiatives. BUMDES Pagerharjo can create jobs, boost local revenue, and bolster the local economy by empowering the people and opening up business options.